Hunger by the Sea: Partnerships in the brave third space. - Han, Xue; McDougall, Julian; Mott, Charlie; Sudbury, Sue (International Journal for Students as Partners, 2018)
In this article, co-authored by two undergraduate students (one international) and two academics in a media faculty of a post-92 university (e.g., Polytechnic), in England, we share the findings and offer a reflexive lens on the process of a media practice education collaboration in the community, through the co-production of the animated film Hunger by the Sea: https://vimeo.com/234840520 . The contributors to this research are media practice academics, media and journalism students from related but distinct disciplines, and the users and providers of a food bank on the English coast. The food bank users and providers have not been involved in this writing, but their voices are (literally) heard in the project’s primary outcome—the animated film. In this article, we articulate reflections on how the project, in bringing together academics, students, and community participants in a challenging but rich space, enabled exchanges of expertise and new, boundary-crossing ways of being in education that can be discussed as “third space” interactions.